Seawater Acidification Exacerbates the Negative Effects of UVR on the Growth of the Bloom-Forming Diatom Skeletonema costatum - Li, Futian; Li, Hangxiao; Xu, Tianpeng; Li, Shihu; Xu, Juntian (Frontiers in Marine Science, 2022)
Climate changes such as seawater acidification caused by rising atmospheric CO2 and increased ultraviolet radiation (UVR) intensity resulting from shoaling of the upper mixed layer may interact to influence the physiological performance of marine primary producers. But few studies have investigated long-term (>30 days) effects of UVR under seawater acidification conditions, along with less attention on the differential effects of long- and short-wavelength UVA. In the present study, four spectral treatments (>280, >320, >360, and >400 nm) under two pCO2 levels (400 and 1,000 μatm) were set to investigate the interactive effects of seawater acidification and UVR on the bloom-forming diatom Skeletonema costatum. The results showed that UVR decreased growth and effective quantum yield of Photosystem II (PSII) by 9%–16% and 11%–24%, respectively, but it enhanced cell sizes significantly. Long- and short-wavelength UVA showed differential effects on cell volume and the effective quantum yield of PSII, especially at the elevated CO2 level. Generally, seawater acidification depressed the effective quantum yield of PSII and cell volume by 6%–18% and 8%–39%, respectively. Additionally, the contents of key PSII proteins (D1 and D2) decreased at the elevated CO2 level. Elevated CO2 significantly increased the inhibition of UVR on growth in the >280 nm spectral treatment when compared with ambient CO2, while it showed no effects in other spectral treatments. Overall, the results indicate that the effects of seawater acidification on the ubiquitous diatom are light wavelength-dependent.